2016
DOI: 10.1002/2016jg003460
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal gradients in tree ring stable carbon and oxygen isotopes reveal differential climate influences of the North American Monsoon System

Abstract: The arrival of the North American Monsoon System (NAMS) terminates a presummer hyperarid period in the southwestern United States (U.S.), providing summer moisture that is favorable for forest growth. Montane forests in this region rely on winter snowpack to drive much of their growth; the extent to which they use NAMS moisture is uncertain. We addressed this by studying stable carbon and oxygen isotopes in earlywood and latewood from 11 sites along a latitudinal gradient extending from Arizona and New Mexico … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
64
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 56 publications
11
64
0
Order By: Relevance
“…Thus, the temporal lag between volumetric growth and carbon allocated to cellulose observed here is consistent with data from the global analysis by Cuny et al () (Figure ). The result is also consistent with recent work on the isotopic composition of cellulose from other conifers in the southwestern United States, which found that the isotopic ratio of cellulose within a tree‐ring correlated most strongly with climate a month or more after the cells formed (Monson et al, ; Szejner et al, ). Taken together, the comparison of the modeled transpiration and photosynthesis with sap flux, satellite GPP, and dendrometry data, all indicate that the modeled seasonal cycle in cellulose is approximately accurate.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, the temporal lag between volumetric growth and carbon allocated to cellulose observed here is consistent with data from the global analysis by Cuny et al () (Figure ). The result is also consistent with recent work on the isotopic composition of cellulose from other conifers in the southwestern United States, which found that the isotopic ratio of cellulose within a tree‐ring correlated most strongly with climate a month or more after the cells formed (Monson et al, ; Szejner et al, ). Taken together, the comparison of the modeled transpiration and photosynthesis with sap flux, satellite GPP, and dendrometry data, all indicate that the modeled seasonal cycle in cellulose is approximately accurate.…”
Section: Resultssupporting
confidence: 91%
“…Until now, limited datasets existed to test how the seasonal origins of plant water varied over timescales longer than one to two growing seasons, which hindered the ability to predict the response of ecosystem productivity, watershed hydrology or soil biogeochemical cycles to long and short term climate forcing (Eissenstat et al, ; Joslin et al, ). The approach takes advantage of the fact that reliance on snowmelt through the growing season would lead to reduced variance in the isotopic ratio of the plant's water source and isotopic cycles in cellulose that would be driven primarily from surface climate and physiological forcing (Barbour et al, ; Gessler et al, ; Roden et al, ; Szejner et al, ). Alternatively, utilization of growing season precipitation would lead to isotopic cycles in the cellulose that reflect both an isotopically dynamic source water and changes in surface climate (Belmecheri et al, ; Treydte et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, as δ 13 C in plants in arid regions is largely a measure of stomatal limitation of photosynthesis, that relationship could also derive indirectly because of the influence of monsoon precipitation on VPD and consequently stomatal conductance, and need not indicate actual use of monsoon precipitation for growth. While we attribute similar alpha cellulose δ 18 O of earlywood and latewood in our study to the use of a common water source, winter precipitation, we acknowledge that this finding is based on only two years' of data (2009)(2010) and when evaluated over a longer time period significant differences may be found [61].…”
Section: Discussionsupporting
confidence: 55%
“…While this finding is possibly attributable to Arizona pines using monsoon rain for latewood growth, it might also indicate greater evaporative enrichment of soil and leaf waters during AZ summers compared to summers in CA and OR. Similarly, ponderosa pine latewood cellulose δ 18 O significantly correlates with summer precipitation and summer VPD in southern AZ and NM, indicating the importance of both monsoon rains and the associated reduction in VPD for latewood production in locations where monsoon rain can make up greater than 50% of annual water inputs [61]. Using δ 13 C, Leavitt et al [41,42] have similarly shown a correlation between latewood cellulose and monsoon precipitation.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have highlighted the importance of the Gulf of Mexico as a moisture source [4] [5]. Despite several aspects of the NAM such as rainfall intensity effects [6], sensitivity to interannual variability [7] and climate influence [8] modes are relatively well known, few studies have addresses the role of the moisture supply for the monsoon activation. Based on observational datasets, the moisture flux was analyzed by [9], and his results showed that moisture flux from the Gulf of Mexico across the Tehuantepec region was sustained during the rainy period.…”
Section: Introductionmentioning
confidence: 99%